Imaging‐based evaluation of pathogenicity by novel DNM2 variants associated with centronuclear myopathy. Issue 2 (19th December 2021) - Fujise, Kenshiro; Okubo, Mariko; Abe, Tadashi; Yamada, Hiroshi; Takei, Kohji; Nishino, Ichizo; Takeda, Tetsuya; Noguchi, Satoru
Abstract: A centronuclear myopathy (CNM) is a group of inherited congenital diseases showing clinically progressive muscle weakness associated with the presence of centralized myonuclei, diagnosed by genetic testing and muscle biopsy. The gene encoding dynamin 2, DNM2, has been identified as a causative gene for an autosomal dominant form of CNM. However, the information of a DNM2 variant alone is not always sufficient to gain a definitive diagnosis as the pathogenicity of many gene variants is currently unknown. In this study, we identified five novel DNM2 variants in our cohort. To establish the pathogenicity of these variants without using clinicopathological information, we used a simple in cellulo imaging‐based assay for T‐tubule‐like structures to provide quantitative data that enable objective determination of pathogenicity by novel DNM2 variants. With this assay, we demonstrated that the phenotypes induced by mutant dynamin 2 in cellulo are well correlated with biochemical gain‐of‐function features of mutant dynamin 2 as well as the clinicopathological phenotypes of each patient. Our approach of combining an in cellulo assay with clinical information of the patients also explains the course of a disease progression by the pathogenesis of each variant in DNM2 ‐associated CNM. Abstract : In cellulo formation of T‐tubule‐like structures (TLS) is defected in the presence of novel dynamin 2 mutants associated with centronuclear myopathy. Microscopic images show FLAG‐tagged wild‐type or mutant dynamin 2 (green) and RFP‐tagged BIN1 (red) in mouse myoblast C2C12 cells.